Adopting drone technology for blood delivery: a feasibility study to evaluate its efficiency and sustainability - Pammi Gauba; Anita Nangia; Shalini Bahadur; Sangeeta Pahuja; Shweta Dang; Rambha Pathak; Kiran Agarwal; Sunita Sharma; Deepti Ambalkar; Manoj Jha; Ranju Singh; Priyanka Virdi; et al. (Archives of Public Health)
Abstract Background Understanding what drives effective implementation is the key to making more sustainable developments. Blood and its components are critical for life-saving transfusions, however, their availability at the point of care is often limited. Moreover, the logistical challenges associated with blood product transport are substantial and maintaining the cold chain throughout the supply route is crucial to sustain their functional integrity as the temperature fluctuations can compromise its oxygen-carrying capacity. Furthermore, factors such as unpredictable demand, remote geographical locations, and extreme climatic conditions can further compound these difficulties. With India’s diverse and distinct topographical variations and geographical spread, last-mile service deliveries of healthcare supplies face multiple challenges. Unmanned Aerial Vehicles (UAVs) or drones are emerging technologies with the potential to leapfrog the last mile logistics solution for transporting medical supplies thus, strengthening the overall healthcare system. Methods This study investigates the impact of drone-based delivery on the quality and stability of blood components, relative to conventional transport methods along with the operational challenges associated with implementing a drone-based blood delivery system. To achieve these objectives, the EPIS (Exploration, Preparation, Implementation, Sustainment) framework was adopted, which facilitates a systematic approach to this complex implementation process. The drone-related technical and logistic challenges encountered during the study were also identified. Results The study documents the challenges experienced by the study team during the drone-based delivery of blood while maintaining the biochemical parameters of blood components. During the drone based transportation the temperature, integrity of blood cells, and other parameters were maintained, while slight changes in few parameters were observed via both transportation modes. In this study the drone travelled around 36 km in 8 min, while van took around 55 min to cover the same distance. Conclusions The present study was done to assess the impact of drone-based delivery on the blood components after the transportation and their comparison to conventional modes of transportation, also, to lay foundation for the successful and sustainable drone-based blood delivery programs. This study suggests that the blood and its components can be transported safely by drone following standard guidelines, which could be helpful particularly in determining blood in emergency situation and difficult terrains.